Endogenous threshold effects and transmission channels of foreign aid on economic growth: Evidence from WAEMU zone countries - Bayale, Nimonka; Traoré, Fousseini; Diarra, Souleymane; Maniraguha, Faustin (Elsevier, 2022)
This paper analyses threshold effects and transmission Channels of foreign aid on economic growth of WAEMU countries using the World Bank, the International Monetary Fund and the International Country Risk Guide databases to cover the period spanning from 1980 to 2018. After applying endogenous threshold approach to determine aid threshold above which its affects growth and estimate its long-term effects, Pagan's *Residual-Generated Regressors* method was used to identify channels that can modulate effects of aid on growth. Evidences strongly support the view that the relationship between aid and economic growth is non-linear with a threshold that lies between 12.37 and 14.08% of GDP. Above these values, the marginal effect of aid is 2.1%. Moreover, results indicate that only investment seems to be a potential channel through which aid would affect growth. Thus, aid within the WAEMU countries is beneficial. Its content and use should be the main concern of donors and policy-makers.